A Quantitative Analysis of the Students’ Experience with Digital Media in L2 Acquisition - Марсель Пікхарт; Лікаа Хабеб Аль-Абайді; Мохсін Абдур Рехман (Психолінгвістика, 2022)
Aim. Foreign language education widely utilizes various forms of eLearning or blended learning techniques and tools, and this trend has recently been supported and speeded up by the global pandemics of COVID-19. The study attempts to analyse the students’ experience with the use of digital media used for foreign language education with the aim of providing clear implications needed for future digital (online) language higher education.